Pengembangan Model Vendor Managed Inventory dengan Banyak Retailer yang Mempertimbangkan Ketidakpastian Lead Times - Carles Sitompul; Paulina Ariningsih; Ida Bagus Deva Narswara Santosa (Jurnal Rekayasa Sistem Industri, 2018)
An inventory management system in supply chains called Vendor Managed Inventory (VMI) is very promising due to the cost efficiency resulted from implementing such system. This research aims to develop a vendor managed inventory for multiple retailers. The model also takes into account lead time uncertainties from vendor to its retailers. A mathematical formulation for VMI with multiple retailers is first developed using deterministic lead times.  Subsequently, lead times uncertainties are then taken into account where modes lead times are broken into two components: modes and delays, each with their respective probabilities. In turn, an approximation model is used to solve the problem because the complexity aroused from the model is difficult to solve using analytical methods. It is shown that the proposed approximation method is able to solve VMI problem with multiple retailers and uncertain lead times.  Furthermore, the total inventory cost is significantly reduced when compared to the usual economic order quantity method because stockouts are less frequent.